Pengembangan Sumber Daya Berbasis Teknologi Digital, Pelaporan Keuangan, Pemasaran dan Pengelolaan SDM Bisnis Kuliner Lokal - Putu Gede Wisnu Permana Kawisana; Ni Kd Sioaji Yamawati; I Gde Agung Wira Pertama (Community Service Journal (CSJ), 2024)
Mas Ubud Village is not only known as a center for wood arts and crafts, but also serves a culinary experience rich in local wisdom and authentic Balinese flavors. So far, processed Ubud duck has become a hallmark of high-end tourist local food while micro, small and medium (MSME) culinary businesses such as street food also have great potential in reaching international markets such as tourism countries in Asia: Thailand, Korea, Japan and others. Warung Kuah Pindang which is located in Mas village, Ubud is a culinary business in the middle of rice fields with Balinese architecture, namely bale roofed with reeds which serves Balinese street food (Balinese local cuisine) as the main menu that is actually able to attract the attention of domestic and international tourists. In addition, this place has great potential in the advancement of superior business development. Apart from the smooth running of business and consumer interest, there are problems faced by partners during the running of their business. This problem is summarized by the service team as follows. 1) Financial recording that is still manual and unsystematic, 2) Partners have the potential to reach international market share but do not have the knowledge and ability, 3. Low employee performance is motivated by unclear job desks and non-skilled recruitment processes. The solutions offered to partners are in the form of: 1) Training in recording financial transactions and providing a digitized financial recording system, 2) Socialization and assistance in foreign language international marketing management through digitalization in reaching the international market, 3) Socialization and assistance in human resource development in improving employee performance to advance service quality